The Beauty of Musculoskeletal Ultrasound: Spot Diagnoses - Drakonaki, Elena E; Martinoli, Carlo; Vanhoenacker, Filip Maria; Detoraki, Anna; Dalili, Daniel E; Adriaensen, Miraude (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2023)
Introduction Ultrasound is a powerful technique in musculoskeletal (MSK) imaging, and it can replace MR imaging in many specific clinical scenarios. This article will feature some common and less common spot diagnoses in musculoskeletal ultrasound.Spot diagnosis Cases were collected by members of the Educational Committee of the ESSR ( European Society of Musculoskeletal Radiology) with expertise in musculoskeletal ultrasound. Sixteen clinical entities are discussed based on the features that allow US spot diagnosis.Conclusion Clinical history, location, and ultrasound appearance are the keys to spot diagnoses when performing musculoskeletal ultrasound.Key Points: Citation Format
Keywords: soft tissues; ultrasound; anatomy